2019
DOI: 10.1186/s12974-019-1435-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic blockade of HMGB1 reduces early motor deficits, but not survival in the SOD1G93A mouse model of amyotrophic lateral sclerosis

Abstract: Background Amyotrophic lateral sclerosis (ALS) is a fatal and rapidly progressing neurodegenerative disease without effective treatment. The receptor for advanced glycation end products (RAGE) and the toll-like receptor (TLR) system are major components of the innate immune system, which have been implicated in ALS pathology. Extracellularly released high-mobility group box 1 (HMGB1) is a pleiotropic danger-associated molecular pattern (DAMP), and is an endogenous ligand for both RAGE and TLR4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 51 publications
4
24
0
Order By: Relevance
“…The present study clearly demonstrated a marked reduction in overall inflammatory markers in the spinal cord including decreases in pro-inflammatory cytokines TNF α and IL-1β, the RAGE ligand and danger-associated molecular pattern molecule HMGB1, innate immune receptors TLR4 and C5aR1, inflammasome component NLRP3, and an oxidative stress marker. This is consistent with many prior studies demonstrating these components play pathogenic roles in ALS disease progression [35,36,40-43,20,19,37,44]. Interestingly, genetic deletion of RAGE also resulted in a down-regulation of the complement components C1qb and C3.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study clearly demonstrated a marked reduction in overall inflammatory markers in the spinal cord including decreases in pro-inflammatory cytokines TNF α and IL-1β, the RAGE ligand and danger-associated molecular pattern molecule HMGB1, innate immune receptors TLR4 and C5aR1, inflammasome component NLRP3, and an oxidative stress marker. This is consistent with many prior studies demonstrating these components play pathogenic roles in ALS disease progression [35,36,40-43,20,19,37,44]. Interestingly, genetic deletion of RAGE also resulted in a down-regulation of the complement components C1qb and C3.…”
Section: Discussionsupporting
confidence: 92%
“…It is now well documented that RAGE and its pro-inflammatory ligands are potentially involved in ALS, with evidence from both human patients and rodent models [6,10,11,13,20,19,12]. The present study further adds to this knowledge demonstrating alteration of RAGE mRNA expression in the spinal cord and skeletal muscle of multiple preclinical transgenic ALS mouse models including SOD1 G93A , TDP43 Q331K and TDP43 WTxQ331K mice, suggestive of a common activation pathway for RAGE upregulation in these models, that is independent to the underlying genetic driver of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed acute (1 day) and chronic (1 month) DAMP transcript upregulation in both immune (dendritic cells, T‐cells, macrophages, and neutrophils) and non‐immune (fibroblasts, endothelial cells, and tissue progenitor cells) suggesting that low‐level tissue damage may drive local inflammation and persistent tissue dysfunction. Considering recent advances targeting specific DAMP molecules 47,48 or broad classes of pro‐inflammatory DAMPs 49 to mitigate acute sepsis mortality, 50 it would be interesting to determine the extent to which DAMP/PAMP reduction would aid post‐sepsis muscle and fat tissue repletion.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reported therapeutic failures with the m2G7 in preclinical trials. Administration of m2G7 in a mouse model of amyotrophic lateral sclerosis showed overall very limited efficacy (59).…”
Section: Islet Transplantation In Diabetic Micementioning
confidence: 99%